Dinamika Pendidikan Anak Usia Dini: Perubahan Kurikulum 2013 ke Kurikulum Merdeka - Apriliani, Silvi; Nur Azizah, Alisah; Zahra, Anita; ma’sum aprily, Nuraly (Journal of Childhood Education, Development and Parenting, 2024)
The curriculum is the solid foundation of a learning process. The curriculum is considered very important, seeing as it contains an educational plan that explains the materials, methods and assessments in the learning system. However, the phenomena that exist in society when the climate changes change over time, this is a common occurrence in the world of education. The change in the curriculum has a strong reason because it is an effort to improve the previous curriculum. The field of early childhood education has experienced curriculum changes, for example, improving the 2013 curriculum to an independent curriculum has increased the quality of education and students' ability to adapt. The research method used is a library study where the collection of information comes from Google Scholar published in the last five periods, starting from 2019-2023, which is presented in the form of a description. The aim of this research includes the changes that occurred when the 2013 curriculum was replaced by the independent curriculum in the Early Childhood Education unit. The results show that this curriculum change effort is a complement to the previous curriculum, however, the prominent difference is seen in the approach used, focus and includes the curriculum itself in order to create optimal learning amidst current technological developments.